Correlation between crash temporal-spatial pattern and crash injury types at east coast expressway phase 2 - Nor Azira, Rasedi (2017)
Road traffic crashes are the foremost causes of death and disability globally, with a top-heavy number occurring in developing countries. Crashes are currently ranked ninth globally amongst the leading causes of disability and the ranking is anticipated to rise to rank third by 2020. Over 1.2 million peoples die every year in the world’s roads. The aim of this study is to get correlations of road traffic crashes related issues of East Coast Expressway Phase 2 in terms of time and space with crash type from 2013 to 2015. The necessary data for the study was collected from Traffic Branch, Royal Malaysian Police, Terengganu Contingent. Data Analysis was made by using Microsoft Excel 2010 and SPSS version 22. The results were presented in the form of line graphs, column graphs, pie charts and correlations. The result of the study revealed that, 1586 road traffic crashes have occurred in the highway within the study period. Hulu Terengganu categorized as black spot areas in this highway which number of severities recorded are large with 58% for fatal crashes, 33% for crashes with severe injuries and 32% for crashes with slight injuries. The time between 12 pm to 6 pm reveals as the largest proportion of all road traffic crashes scenes. Overall, correlations between crash temporal-spatial pattern and crash type showed weak correlations. In conclusion, it probably can be another reason that can caused of crashes at East Coast Expressway Phase 2. Human factors such as driving while sleepy, exceeding the gazetted speed limit, negligence and failure to comply with safety requirements were suspected to be one of the major causes contributing to this problem.